A Register of Debts Owed to Jews, Confiscated in 1349: What it Tells Us about Moneylending Practices - Cluse, Christoph (Aschkenas, 2025)
This article deals with two registers of outstanding loans contracted with Jewish moneylenders in the town of Mons and its surroundings (county of Hainaut). They were drawn up in the course of the persecutions at the time of the Black Death, during the summer of 1349. It is claimed that the registers, at least in part, constitute translations from the Hebrew account books kept by the moneylenders themselves. Where they give details, they allow insights into the Jews’ accounting practices, offering rare additions to what we know from the few extant Hebrew account books of the later medieval period. This concerns, inter alia , the practice of calculating interest. Given the short-term nature of the loan contracts, compound interest could accrue.